Dark sacred night - Connelly, Michael, 1956- (Little, Brown and Company, 2018)
Detective Renée Ballard is working the night beat -- known in LAPD slang as "the late show" -- and returns to Hollywood Station in the early hours to find a stranger rifling through old file cabinets. The intruder is retired detective Harry Bosch, working a cold case that has gotten under his skin. Ballard can't let him go through department records, but when he leaves, she looks into the case herself and feels a deep tug of empathy and anger. She has never been the kind of cop who leaves the job behind at the end of her shift -- and she wants in. The murder, unsolved, was of fifteen-year-old Daisy Clayton, a runaway on the streets of Hollywood who was brutally killed, her body left in a dumpster like so much trash. Now Ballard joins forces with Bosch to find out what happened to Daisy, and to finally bring her killer to justice. Along the way, the two detectives forge a fragile trust, but this new partnership is put to the test when the case takes an unexpected and dangerous turn.